Early Left Ventricular Structural Changes With Preserved Function in Overweight and Obese Adolescents: A Speckle-Tracking Echocardiography Study - Nurfandi, Wendi; Hafsah, Tisnasari; Rahayuningsih, Sri Endah; Apandi, Putria Rayani; Hakim, Dzulfikar Djalil Lukmanul; Ghrahani, Reni; Kuswiyanto, Rahmat Budi; Gurnida, Dida Akhmad (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Overweight and obesity in adolescents are associated with dyslipidemia and may contribute to early cardiovascular remodelling. Speckle-tracking echocardiography (STE) is a sensitive imaging technique capable of detecting early myocardial functional alterations before the onset of clinical symptoms. This study aimed to evaluate the correlation between cardiac chamber dimensions, left ventricular (LV) geometry and function, and lipid profiles in overweight and obese adolescents. Methods: A cross-sectional study was conducted from June to September 2023, involving 51 overweight and obese adolescents aged 15–18 years in Bandung, Indonesia. Anthropometric measurements, fasting lipid profiles (triglycerides, total cholesterol, LDL, HDL), and transthoracic echocardiography were obtained. LV dimensions, LV mass index (LVMI), ejection fraction (EF), fractional shortening (FS), and global longitudinal strain (GLS) were assessed. Associations were analyzed using Pearson correlation.Results: Participants were predominantly male (64.7%) with a mean age of 16.3±0.6 years. Overweight (47.1%) and obesity (52.9%) were almost equally distributed with a mean BMI of 29.6±4.1 kg/m². LVMI correlated negatively with total cholesterol (r=−0.356; p=0.005), HDL (r=−0.351; p=0.006), and LDL (r=−0.280; p=0.023). The LV posterior wall thickness and LV end-diastolic diameter were also inversely correlated with selected lipid parameters. Interventricular septal thickness in systole correlated positively with triglycerides (r=0.270; p=0.028). No significant correlations were found between lipid profiles and LV function parameters, including EF, FS, and GLS (p>0.05).Conclusions: In overweight and obese adolescents, lipid profiles are associated with early alterations in LV structural dimensions while LV systolic function remains preserved. These findings support the importance of early cardiovascular screening and lifestyle modification to reduce future cardiometabolic risk.